2015
DOI: 10.3389/fimmu.2015.00330
|View full text |Cite
|
Sign up to set email alerts
|

Human and Mouse Mononuclear Phagocyte Networks: A Tale of Two Species?

Abstract: Dendritic cells (DCs), monocytes, and macrophages are a heterogeneous population of mononuclear phagocytes that are involved in antigen processing and presentation to initiate and regulate immune responses to pathogens, vaccines, tumor, and tolerance to self. In addition to their afferent sentinel function, DCs and macrophages are also critical as effectors and coordinators of inflammation and homeostasis in peripheral tissues. Harnessing DCs and macrophages for therapeutic purposes has major implications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
140
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 236 publications
(339 reference statements)
2
140
0
Order By: Relevance
“…In contrast to murine samples, which allow the use of truly na€ ıve and age-matched samples, this is not possible for the human setting. This might be especially interesting in the light of an ongoing discussion about the reliability of animal models to study human immune activation (Mestas and Hughes, 2004;Reynolds and Haniffa, 2015;Shay et al, 2013). In contrast, the average donor age for the glioblastoma samples was 59 years.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to murine samples, which allow the use of truly na€ ıve and age-matched samples, this is not possible for the human setting. This might be especially interesting in the light of an ongoing discussion about the reliability of animal models to study human immune activation (Mestas and Hughes, 2004;Reynolds and Haniffa, 2015;Shay et al, 2013). In contrast, the average donor age for the glioblastoma samples was 59 years.…”
Section: Discussionmentioning
confidence: 99%
“…After internalization, phagocytosed bacteria are intracellularly killed via oxygen-dependent or -independent mechanisms [7,16,17]. Studies have demonstrated that treatment with rapamycin decreased ROS generation, NO production and NF-κB activation in LPS-activated rat hepatocytes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Mononeuclear phagocyte system (MPS) is one of the most important components in the host immune system [7]. MPS system consists of the phagocytic cells located in reticular connective tissue, including monocytes, macrophages, as well as specialized macrophages like Kupffer cells, Langerhans cells, microglia and osteoclasts [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes, macrophages and dendritic cells (DCs) have an important role in tissue homeostasis, innate immune responses and initiation of adaptive immunity and traditionally comprise the mononuclear phagocyte system 1 , 2 . Recent data based predominantly on experiments in the mouse suggest that their ontogeny is rather diverse: monocytes and DCs are short‐lived bone marrow‐derived leukocytes that share the monocyte–macrophage DC progenitor as their last common haematopoietic precursor 1 , 3 .…”
mentioning
confidence: 99%